2019
DOI: 10.1007/s13592-019-00646-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding of honey to assess differences in plant-pollinator interactions between urban and non-urban sites

Abstract: Ever-faster rates of urbanization have led to the substantial loss of agricultural land and natural areas. Furthermore, vegetated land is often fragmented and dominated by nonnative plant species within urban areas, which is likely to impact plant-pollinator interactions. However, the study of plant-pollinator interactions is labor intensive and remains challenging. Here, we compared plant species visited by honeybees in urban versus non-urban sites, using metabarcoding to identify pollen in honey samples. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…This result is congruent with Lucek et al. (2019) which found that honey samples from more urban sites in Switzerland tended to have higher floral diversity, though this difference was not found to be significant. However, we caution that the site‐level replication of our study is not sufficient to draw firm conclusions about the relationship between urban and agricultural land use and honeybee forage dynamics in the Midwest.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is congruent with Lucek et al. (2019) which found that honey samples from more urban sites in Switzerland tended to have higher floral diversity, though this difference was not found to be significant. However, we caution that the site‐level replication of our study is not sufficient to draw firm conclusions about the relationship between urban and agricultural land use and honeybee forage dynamics in the Midwest.…”
Section: Discussionsupporting
confidence: 90%
“…The question of how honeybee foraging behaviour responds to the unique challenges of urban and agricultural landscapes is salient from both basic and applied perspectives (Couvillon et al., 2014a; Härtel & Steffan‐Dewenter, 2014). With respect to urban land use, recent empirical studies have described honeybee (Lau et al., 2019; Lucek et al., 2019) diet and foraging distance (Garbuzov et al., 2015). The only study, however, to articulate a theoretical relationship between honeybee foraging behaviour and suburban land use is that of Waddington et al.…”
Section: Introductionmentioning
confidence: 99%
“…The question of how honey bee foraging behavior responds to the unique challenges of urban and agricultural landscapes is salient from both basic and applied perspectives (Couvillon et al 2014a, Härtel andSteffan-Dewenter 2014). With respect to urban land use, recent empirical studies have described honey bee (Lau et al 2019, Lucek et al 2019) diet and foraging distance (Garbuzov et al 2015). The only study, however, to articulate a theoretical relationship between honey bee foraging behavior and suburban land use is that of Waddington et al (1994), where the authors suggest that the fine-grain pattern of floral patch distribution typical of suburban landscapes favors independent patch discovery over the use of waggle dance recruitment by foraging honey bees.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, four datasets were obtained by processing pollen found in nests or carried on insects bodies (Bell et al, 2017; Biella et al, 2019; Vaudo et al, 2020; along with the unpublished one, hereafter Tommasi et al, unpublished, that contains information about interactions between 249 insects and 156 plants). Three dataset comes from honey sample analysis (Lucek et al 2019; DeVere et al, 2017; Jones et al, 2021), and one was obtained from the analysis of pollen mock samples specially constructed for methodological assessments (Bell et al, 2019).…”
Section: Resultsmentioning
confidence: 99%